Julius Chambers : A Life in the Legal Struggle for Civil Rights - Rosen, Richard A., 1947-; Mosnier, Joseph (Book collections on Project MUSE., 2016)
Born in Mount Gilead, North Carolina, Julius Chambers (1936-2013) escaped the fetters of the Jim Crow South to emerge in the 1960s and 1970s as the US's leading African American civil rights attorney. In this biography, Richard A. Rosen and Joseph Mosnier connect the details of Chambers's life to the wider struggle to secure racial equality through the development of modern civil rights law.